Beamforming for Cooperative Retransmission via User Relaying in Multiple-Antenna Cellular Systems - Ryu, Jong Yeol; Choi, Wan; Kim, Dong In; Schober, Robert (IEEE Transactions on Wireless Communications, 2014)
We propose a novel cooperative user relaying scheme for a two-user multiple-antenna downlink cellular system where each user has to receive a certain required amount of information. A user who successfully receives its required amount of information is supposed to help the other user in receiving its required amount of information through cooperative user relaying. For the proposed cooperative user relaying scheme, we jointly design linear beamformers at the base station over three transmission phases to minimize the total transmission time required for both users to receive their respective required amounts of information, which turn out to be approximated equivalent to the maximization of the sum throughput. In addition, considering a practical hybrid automatic repeat request (HARQ) protocol with user relaying, we modify the proposed scheme to minimize the required number of retransmissions. Our numerical results show that the proposed cooperative user relaying scheme achieves substantial gains over conventional transmission without user relaying in terms of both the average sum throughput and the transmission failure probability.<br
Keywords: Antennas; Throughput; Array signal processing; Silicon carbide; Downlink; Relays; Wireless communication